Inhibition of Cdk8/Cdk19 Activity Promotes Treg Cell Differentiation and Suppresses Autoimmune Diseases - Guo, Zengli; Wang, Gang; Lv, Yanfang; Wan, Yisong Y.; Zheng, Junnian (Frontiers in Immunology, 2019)
Foxp3 expressing regulatory T (Treg) cells, as the central negative regulator of adaptive immune system, are essential to suppress immune response and maintain immune homeostasis. However, the function of Treg cells is frequently compromised in autoimmunity and hyper-activated in infections and tumor microenvironments. Thus, manipulating Treg cells becomes a promising therapeutic strategy for treating various diseases. Here we reported that inhibition of Cdk8/Cdk19 activity by small molecule inhibitors CCT251921 or Senexin A greatly promoted the differentiation of Treg cells and the expression of Treg signature genes, such as Foxp3, CTLA4, PD-1 and GITR. Mechanistically, we found that the augmented Treg cell differentiation was due to sensitized TGF-β signaling by Cdk8/Cdk19 inhibition, which was associated with attenuation of IFN-γ-Stat1 signaling and enhancement of phosphorylated Smad2/3. Importantly, treatment with Cdk8/Cdk19 inhibitor CCT251921 significantly increased Treg population and ameliorated autoimmune symptoms in an experimental autoimmune encephalomyelitis (EAE) model. Taken together, our study reveals a novel role of Cdk8/Cdk19 in Treg cell differentiation and provides a potential target for Treg cell based therapeutics.